From rogue to everyman : a foundling's journey to the Bastille - Bongie, Laurence L. (McGill-Queen's University Press, 2004)
Julie knew intimately the sights, sounds, and smells of the French capital, its Opera and playhouses, law courts, narrow dirty streets, hackney coaches, great houses, low taverns, and splendid public gardens. Working first as an informer and later as a police officer, he came to know only too well the activities of the capital's rakes, thieves, loan sharks, pickpockets, confidence men, blackmailers, crooked gamblers, and rowdy bullying soldiers, not to mention its twenty or thirty thousand prostitutes - all closely watched by as many as three thousand government spies and the eighteenth-century world's most invasive police network. Julie established close contacts with a number of the capital's leading "maquerelles" as well as their distinguished clients, and his underground news sheets, lifted mainly from secret vice squad reports, provided a restricted circle of wealthy subscribers with racy accounts of the town's sexual dalliances. His story ends in the dreaded Bastille. Extensive "ations from Julie's writings trace the moral itinerary of a clever, manipulating rogue, spirited liar, thief, poetaster, and libertine.